Hubungan antara Dukungan Sosial Keluarga dengan Tingkat Kepercayaan Diri pada Generasi Z - Ester Vani Tria Wardani; Yohanes Heri Widodo (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study employed a quantitative method with a correlational research design to examine the relationship between family social support and self-confidence among Generation Z individuals born between 1997 and 2012. A total of 205 respondents participated in this study. Data were collected using two Likert-scale instruments: the Family Social Support Scale (60 items; Cronbach’s Alpha = 0.980) and the Self-Confidence Scale (58 items; Cronbach’s Alpha = 0.939), both demonstrating excellent reliability. Assumption testing indicated that normality and linearity were not met; therefore, the Spearman’s Rho non-parametric correlation test was applied. The results revealed a significant positive relationship between family social support and self-confidence (r = 0.429, p < .001), indicating that higher levels of perceived family support are associated with higher levels of self-confidence among Generation Z. Most respondents reported high levels of family social support (49%) and self-confidence (65%). Additionally, two items on the family social support scale and four items on the self-confidence scale were identified as having relatively lower scores within the moderate category, suggesting potential topics for future training interventions.